Formation of Pokdarwis in supporting the establishment of the Merbabu slope tourism area in Surodadi Village, Magelang - Barkah Susanto; Nia Kurniati Bachtiar; Laili Qomariyah; Afla Azzahra Putri; Lany Christanty; Lasiona Ravi Nirwana (Universitas Muhammadiyah Magelang, 2022)
Due to a lack of understanding regarding the development of tourist areas, the natural potential of Surodadi Village, Candimulyo, Magelang Regency has not been optimally developed to become a natural tourist attraction. This community service's goal is to help create tourism awareness groups (POKDARWIS) and educate people on how to manage and develop natural tourism villages. This program uses the knowledge and skill transfer method to village officials and the community as POKDARWIS candidate members. The result of this program was the formation of POKDARWIS as one of the institutions that handles the development or establishment of tourist areas in Surodadi Village, Candimulyo, Magelang Regency.